Meta-Analysis of Risk Factors for Development of Liver Cirrhosis in Chronic Hepatitis B Patients - Gaofeng Cai; Yongdi Chen; Li Li; Biao Zhou; Chonggao Hu; Yanhong Yu; Mengxin Xu; Qiaolu Hong; Zhengting Wang; Kui Liu; Zhifang Wang; Zhenggang Jiang; et al. (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2018)
Chronic hepatitis B virus (HBV) infection and chronic hepatitis C virus (HCV) are main reasons for the development of liver cirrhosis (LC) on a worldwide scale. Chronic HBV infection is a main reason for the development of LC in high-risk areas, for example, China and Africa, whereas chronic HCV infection is a main reason in developed countries. In China, the harm of LC is serious, and 30 million of chronic hepatitis B (CHB) patients is the major source of LC and the one-year cumulative incidence rate of LC in CHB patients was 2.1% - 6%. The risk factors of the development of LC in CHB patients reported were controversial.  Therefore, we took CHB as participants, and we searched for studies in Chinese Medical Journal Database, Pubmed, Elsevier, Springer, Wiley, OVID, and EBSCO via BoKu data service platform, and did a meta-analysis and evaluated whether those published risk factors changed the development risk of LC. Both odds ratio (OR) and mean difference (MD) with 95% confidence intervals (CI) were calculated by Review Manager 5.0. In this meta-analysis, 2928cases and 6530controls from 29 studies were analyzed. The pooled OR with 95% CI for 5 factors analyzed were: drinking alcohol 1.32 (1.11, 1.59), cigarette smoking 1.26 (1.04, 1.52), hepatitis B e antigen (HBeAg) seropositivity 0.42 (0.19, 0.94), a family history of hepatitis B 1.95 (1.05, 3.62), and male gender 1.33 (1.08, 1.65), respectively. And the pooled MD with 95% CI for 6 factors analyzed were: serum aspartate aminotransferase/alanine aminotransferase (AST/ALT ) ratio 0.29(0.18,0.39), serum total bilirubin (TBil) levels 8.25(5.58,10.92)umol/L, duration of hepatitis B 2.68(2.21,3.15) years, age 7.37(4.60,10.14)years, serum alpha fetoprotein (AFP) levels -0.91(-16.04,14.22)ug/L, and serum HBV DNA levels 0.37 (-0.28, 1.02)copies/ml, respectively.  In CHB patients, habits of drinking alcohol and cigarette smoking, elevated serum levels of TBil and serum AST/ALT ratio, increased duration of hepatitis B, a family of hepatitis B, male gender and older age can increase the risk of LC development.